2014
DOI: 10.1111/wbm.12042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the rice hull‐induced germination of Monochoria vaginalis seeds in darkness

Abstract: The seeds of Monochoria vaginalis require light to germinate. However, they are able to germinate in darkness in the presence of rice hulls. The mechanism of this phenomenon was investigated in this study, in which only the unsterilized seeds of Monochoria were induced to germinate by the presence of a rice hull extract. The rice hull extract was able to be replaced by either a mixture of amino acids and phosphate or a yeast extract. The culture media in which germination was observed always showed turbidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…The extracts of rice hulls have been reported to stimulate germination of Monochoria in both light [14,15] and darkness but with unsterilized rice hulls [10]. However, findings of this study, in contrast, showed that aqueous extracts of rice hulls did not provide induction of Monochoria germination.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…The extracts of rice hulls have been reported to stimulate germination of Monochoria in both light [14,15] and darkness but with unsterilized rice hulls [10]. However, findings of this study, in contrast, showed that aqueous extracts of rice hulls did not provide induction of Monochoria germination.…”
Section: Discussioncontrasting
confidence: 91%
“…However, findings of this study, in contrast, showed that aqueous extracts of rice hulls did not provide induction of Monochoria germination. In this study, the concentration was 1000 ppm using only distilled water, but in the previous researches, the extracts from rice hulls were the combination of both distilled water and methanol [10] and ethyl acetate [15], which may contribute to the different results obtained from this study. However, Yokota et al [10] reported that in darkness, sterilized rice hulls gave no induction of Monochoria germination, and explained that bacteria such as Bacilus sp., Pedobacter sp., and Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations